1992
DOI: 10.1126/science.1496376
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of an RNA Enzyme

Abstract: An in vitro evolution procedure was used to obtain RNA enzymes with a particular catalytic function. A population of 10(13) variants of the Tetrahymena ribozyme, a group I ribozyme that catalyzes sequence-specific cleavage of RNA via a phosphoester transfer mechanism, was generated. This enzyme has a limited ability to cleave DNA under conditions of high temperature or high MgCl2 concentration, or both. A selection constraint was imposed on the population of ribozyme variants such that only those individuals t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
213
0
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 425 publications
(224 citation statements)
references
References 69 publications
3
213
0
8
Order By: Relevance
“…Prior to performing NAIM with a complete series of analogues, it was necessary to identify a reaction condition that was selective, but had a minimum number of uninformative sites due to strong phosphorothioate interference+ Previous experiments with the Tetrahymena group I intron have shown that AaS incorporation can inhibit splicing activity (Deeney et al+, 1987), although the number and location of the detrimental sites varied with the experimental conditions (e+g+, temperature, salt concentrations, incubation time), and the category of ribozyme reaction being studied (39 splice site hydrolysis, 39 splicing by CU addition, or 59-exon cleavage by G; Waring, 1989;Christian & Yarus, 1992, 1993)+ Some of the apparent differences between these experimental results can be explained by experiments that allowed the splicing reaction to proceed too far to completion, which reduced the experimental signal (Waring, 1989), or by experiments that used primer extension to identify the sites of interference, which introduced excessive background noise into the data (Christian & Yarus, 1993)+ Nevertheless, there are some real, and possibly significant, differences in the phosphorothioate interference patterns observed for the first versus the second step of splicing, although it is still difficult to make conclusions about the importance of these differences+ For ease and efficiency of experimental analysis, we elected to study the 39-exon ligation reaction (Beaudry & Joyce, 1992;Mei & Herschlag, 1996)+ This reaction, wherein the 39-OH of the terminal G (G414) nucleophilically attacks an oligonucleotide substrate that mimics the 59-39 ligated exons, is analogous to the reverse of the second step of splicing+ The reaction transfers the 39-exon onto the 39 end of the RNA, and presents three very important advantages over previous efforts to map sites of phosphorothioate interference in the Tetrahymena group I intron+ (1) Using a 39-radiolabeled substrate, the active molecules in the ribozyme population become radioactively labeled during the ligation reaction+ No additional purification of the RNA is necessary prior to iodine treatment and gel electrophoresis, which makes it possible to directly visualize the interference pattern without using reverse transcriptase+ (2) Ease of the reaction makes it feasible to compare interference patterns under a variety of reaction conditions+ (3) Unlike the self-splicing reactions studied previously, the substrate in the reaction is a synthetic oligonucleotide that can be altered chemically to adjust the selectivity of the reaction+ We found the reaction to be maximally informative using a substrate with a 29-deoxy substitution at the cleavage site [dT(-1)S: CCCUCdTAAAAA] in a reaction buffer containing 3 mM MgCl 2 and 1 mM Mn(OAc) 2 + The 29-deoxy substitution reduces the rate of chemistry by more than 1,000-fold (Herschlag et al+, 1993b), which slows the reaction sufficiently that more subtle effects on activity can be detected+ The low metal concentration partially destabilizes the structure of the ribozyme, but the presence of a small amount of the thiophilic manganese ion minimizes the phosphorothioate effects that are present at several positions throughout the intron (Christian & Yarus, 1993)+ Under these conditions, ...…”
Section: Phosphorothioate Interferencementioning
confidence: 99%
See 3 more Smart Citations
“…Prior to performing NAIM with a complete series of analogues, it was necessary to identify a reaction condition that was selective, but had a minimum number of uninformative sites due to strong phosphorothioate interference+ Previous experiments with the Tetrahymena group I intron have shown that AaS incorporation can inhibit splicing activity (Deeney et al+, 1987), although the number and location of the detrimental sites varied with the experimental conditions (e+g+, temperature, salt concentrations, incubation time), and the category of ribozyme reaction being studied (39 splice site hydrolysis, 39 splicing by CU addition, or 59-exon cleavage by G; Waring, 1989;Christian & Yarus, 1992, 1993)+ Some of the apparent differences between these experimental results can be explained by experiments that allowed the splicing reaction to proceed too far to completion, which reduced the experimental signal (Waring, 1989), or by experiments that used primer extension to identify the sites of interference, which introduced excessive background noise into the data (Christian & Yarus, 1993)+ Nevertheless, there are some real, and possibly significant, differences in the phosphorothioate interference patterns observed for the first versus the second step of splicing, although it is still difficult to make conclusions about the importance of these differences+ For ease and efficiency of experimental analysis, we elected to study the 39-exon ligation reaction (Beaudry & Joyce, 1992;Mei & Herschlag, 1996)+ This reaction, wherein the 39-OH of the terminal G (G414) nucleophilically attacks an oligonucleotide substrate that mimics the 59-39 ligated exons, is analogous to the reverse of the second step of splicing+ The reaction transfers the 39-exon onto the 39 end of the RNA, and presents three very important advantages over previous efforts to map sites of phosphorothioate interference in the Tetrahymena group I intron+ (1) Using a 39-radiolabeled substrate, the active molecules in the ribozyme population become radioactively labeled during the ligation reaction+ No additional purification of the RNA is necessary prior to iodine treatment and gel electrophoresis, which makes it possible to directly visualize the interference pattern without using reverse transcriptase+ (2) Ease of the reaction makes it feasible to compare interference patterns under a variety of reaction conditions+ (3) Unlike the self-splicing reactions studied previously, the substrate in the reaction is a synthetic oligonucleotide that can be altered chemically to adjust the selectivity of the reaction+ We found the reaction to be maximally informative using a substrate with a 29-deoxy substitution at the cleavage site [dT(-1)S: CCCUCdTAAAAA] in a reaction buffer containing 3 mM MgCl 2 and 1 mM Mn(OAc) 2 + The 29-deoxy substitution reduces the rate of chemistry by more than 1,000-fold (Herschlag et al+, 1993b), which slows the reaction sufficiently that more subtle effects on activity can be detected+ The low metal concentration partially destabilizes the structure of the ribozyme, but the presence of a small amount of the thiophilic manganese ion minimizes the phosphorothioate effects that are present at several positions throughout the intron (Christian & Yarus, 1993)+ Under these conditions, ...…”
Section: Phosphorothioate Interferencementioning
confidence: 99%
“…The Tetrahymena group I intron is one of several large catalytically active RNAs that folds into a compact globular structure (Fig+ 1;Cech, 1993)+ The intron catalyzes two transesterification reactions in the course of RNA self-splicing (Cech et al+, 1992)+ The first step consists of nucleophilic attack at the 59 splice site by the 39-OH of an exogenous guanosine cofactor+ In the second step, the 59-exon attacks the 39 splice site to produce ligated exons+ Under the appropriate conditions, the intron can also catalyze the reverse of either of these two reactions, resulting in exon ligation back onto the intron (Fig+ 2A;Woodson & Cech, 1989;Green et al+, 1990;Beaudry & Joyce, 1992)+ To understand the reaction specificity and catalytic rate enhancement achieved by this ribozyme, it is necessary to understand the structural basis of intron function+ Improved atomic resolution biochemical methods are needed to identify the specific chemical groups within the intron that are essential to its activity and, as a consequence, perhaps identify unique biochemical signatures for specific RNA structural motifs+…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first environment we supplied a ribozyme population with a "native" RNA oligonucleotide. Cleavage of this oligonucleotide results in the ligation of a portion the substrate to the 3'-end of the ribozyme, and we can exploit this sequence modification to selectively amplify catalytically successful molecules (Beaudry and Joyce 1992;Lehman and Joyce 1993). Molecules with higher activity are more likely to be replicated.…”
mentioning
confidence: 99%